Left traumatic hernia of lateral abdominal wall.: Herida penetrante lumbar derecha - Croci, Fabio; Benquet, Sergio; Pérez Penco, Ernesto (Cirugía del Uruguay, 1987)
A case of penetratlng injury of abdomen due to a knife wound wlth a rare dlreclion that determinate a mesocolonlc and colonic and the immediate formation of a left traumatic hernia of lateral abdominal wall. Sorne considerallons about parietal leslons in abdominal trauma are done.